Identification of Factors Influencing Health Workers' Resistance to Patient Safety Culture at Hospital X Surabaya - Edho Yulianto Suwardi; Nyoman Anita Damayanti (Universitas Nahdlatul Ulama Surabaya, 2026)
Implementing patient safety culture is essential to ensuring the accuracy and quality of healthcare services in hospitals. When not effectively enforced, a deficiency in safety culture can lead to significant adverse outcomes not only for patients but also for healthcare workers and the institutions involved. Data from Hospital X in Surabaya indicated that 56 patient safety incidents were reported in 2024, including 23 near-miss incidents, 28 non-injury incidents, and 5 unexpected incidents. This study aims to identify the factors influencing health workers' resistance to patient safety culture at Hospital X in Surabaya through a survey. A quantitative research design employing a cross-sectional approach was employed, with data collected from 267 respondents and analyzed using linear regression. The hospital's implementation of patient safety culture was perceived to be inadequate in several areas: (1) Shift Handover and Information Exchange; (2) Disclosure of Information; (3) Staff Arrangement and Work Rhythm; (4) Response to Errors; and (5) Patient Safety Event Reporting. Conversely, the aspects perceived positively included: (1) Support for Health Service Facilities; (2) Teamwork; (3) Direct Supervisor Support; (4) Communication Errors; and (5) Organizational Learning and Continuous Improvement. One significant factor identified as influencing this outcome is the use of patient safety reporting as a means of organizational learning (p-value 0.02). Enhancing organizational learning, despite perceptions of favorable aspects, could reduce staff resistance to adopting a more robust patient safety culture. Keywords: Patient safety culture, health worker, resistance